Design and performance evaluation of a soft-switched partial-power LLC converter for PV grid integration - Sebin Davis Kurichiparambil; Varghese Jegathesan (Institute of Advanced Engineering and Science, 2026)
This paper presents a soft-switched partial-power LLC converter integrated within a two-stage photovoltaic (PV) and grid-connected system. The proposed architecture combines the advantages of resonant operation and partial power processing to enhance conversion efficiency and reduce switching losses. Maximum power point tracking (MPPT) is achieved through frequency modulation of the LLC converter, while grid synchronization is maintained using a three-phase voltage-oriented control (VOC) inverter. Simulation results in MATLAB/Simulink demonstrate stable zero voltage switching (ZVS) and zero current switching (ZCS) across a wide irradiance range (400-1000 W/m²), enabling the system to achieve peak efficiencies above 98%, which is superior to typical transformerless and interleaved converter topologies reported in recent literature. The proposed soft-switched PPC-LLC architecture offers an efficient and scalable solution for next-generation PV grid interfaces by combining reduced processed power, robust resonant operation, and high-quality grid integration.